ESL and TESL students' perceptions towards the importance of using readers theatre in teaching literature - Norhayati, binti Husain (Universiti Malaysia Sarawak, UNIMAS, 2008)
The aim of this study was to investigate the perceptions of ESL and TESL students in Universiti Malaysia Sarawak (UNIMAS) towards the importance of using Readers Theatre in Teaching Literature. It also to determine ESL and TESL students’ understandings of Readers Theatre, to identify the ESL and TESL students’ perceptions on the importance of using Readers Theatre, and to discover the challenges that ESL and TESL students might perceive in implementing Readers Theatre. 128 participants from the ESL and TESL programme, Faculty of Cognitive Sciences and Human Development were involved in this study and data was collected through questionnaire. Data collected was analyzed by using SPSS 15.0. The findings of the study indicated that majority of the ESL and TESL students showed positive attitudes towards Readers Theatre. Majority of the students understand the main concepts of readers Theatre although some of the students have misconception in Readers Theatre. The findings also indicated the challenges that ESL and TESL students might perceive in implementing Readers Theatre whereas the challenge of time consuming was the major reason that caused them hesitate to use this technique in teaching literature.